Epidemiology of Estrogen and Dementia in Women with Down Syndrome - Schupf, Nicole (Free Radic Biol Med, 2017)
Several lines of investigation have shown a protective role for estrogen in Alzheimer’s disease through a number of biological actions. This review examines studies of the role of estrogen-related factors in age at onset and risk for Alzheimer’s disease in women with Down syndrome, a population at high risk for early onset of dementia. The studies are consistent in showing that early age at menopause and that low levels of endogenous bioavailable estradiol in postmenopausal women with Down syndrome are associated with earlier age at onset and overall risk for dementia. Polymorphisms in genes associated with estrogen receptor activity and in genes for estrogen biosynthesis affecting endogenous estrogen are related to age at onset and cumulative incidence of dementia, and may serve as biomarkers of risk. To date, no clinical trials of estrogen or hormone replacement therapy (ERT/HRT) have been published for women with Down syndrome. While findings from clinical trials of ERT or HRT for dementia have been generally been negative among women in the neurotypical population, the short interval between menopause and onset of cognitive decline, together with a more positive balance between potential benefits and risks, suggests an opportunity to evaluate the efficacy of ERT/HRT for delaying or preventing dementia in this high risk population, although questions concerning the optimal formulation and timing of the hormone therapy are not yet resolved.